Annealing Effect on the Properties of Cu(In0.7Ga0.3)Se2 Thin Films Grown by Femtosecond Pulsed Laser Deposition. Issue 8 (5th June 2013) - Tsai, Mu‐Gong; Tung, Hsien‐Tse; Chen, In‐Gann; Chen, Chia‐Chuan; Wu, Yun‐Fang; Qi, Xiaoding; Hwu, Yeukuang; Lin, Cen‐Ying; Wu, Ping‐Han; Cheng, Chung‐Wei; Brennecka, G. L.
<x xml:space="preserve">Abstract</x> This work reports the crystallization, microstructure, and surface composition of CuIn0.7Ga0.3Se2 (CIGS) thin films grown by femtosecond pulsed laser deposition at different annealing temperatures. The structural and optical properties of the CIGS films were characterized by X‐ray diffraction, Raman scattering, UV‐visible spectroscopy, and Hall effect measurement. The results indicate that binary crystals of CuSe initially formed on the as‐deposited film, but then completely turned into a quaternary chalcopyrite structure after annealing at 400°C. Phase transformation significantly affects the surface morphology, Hall properties, and band gap. Transmission electron microscopy further revealed that an interface between the Mo substrate and CIGS crystallites contains an amorphous layer even at the high temperature of 500°C. For the application of photovoltaic devices, we also report on the photoresponse of both as‐deposited and annealed films as demonstrated by preliminary tests.